THE USE OF ENGLISH LEARNING ACCOUNTS IN INSTAGRAM TO IMPROVE EFL STUDENTS VOCABULARY - Nurkhamidah Putri Wulandari (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Everyone may quickly access all information in this era of the Industrial Revolution 4.0. The technology used to facilitate human activities and give comfort is continually evolving. Digitization occurs in a variety of disciplines, including education. Along with the times, education or knowledge can not only be obtained through formal and non-formal education. Instagram as an application that is widely owned by all ages, provides various features and information that can help students learn English, especially vocabulary. This study aims to find out the use of English learning accounts on Instagram help students increase their vocabulary level and how it can happen. This study is qualitative research, which uses questionnaires as its data collection. The study indicates instagram contains interesting words and images and it is very hepful to improve students vocabualry.